НАЦИОНАЛьНЫЙ ГЕРОЙ В ТРАКТОВКЕ ЕГИПЕТСКОГО ДРАМАТУРГА АЛЬФРЕДА ФАРАГА (ҚазҰУ хабаршысы. Шығыстану сериясы, 2018)
The article presents interpretation of the historical narratives by the famous Egyptian dramatist AlfredFarag. The aim of the research is to open originality of artistic and contextual side of the play (composition)related to interpretation of the role of personality in history. During the research it was identifiedthat the author elucidated his own understanding of such categories as truth and justice by means ofmain hero’s character. The artistic peculiarities of drama: splicing together different story lines, methodof «actor’s improvisation» and elements of «theater in the theater».